Formation of 3D Self‐Organized Neuron‐Glial Interface Derived from Neural Stem Cells via Mechano‐Electrical Stimulation. Issue 19 (4th July 2021) - Tai, Youyi; Ico, Gerardo; Low, Karen; Liu, Junze; Jariwala, Tanvi; Garcia‐Viramontes, David; Lee, Kyu Hwan; Myung, Nosang V.; Park, B. Hyle; Nam, Jin
Abstract: Due to dissimilarities in genetics and metabolism, current animal models cannot accurately depict human neurological diseases. To develop patient‐specific in vitro neural models, a functional material‐based technology that offers multi‐potent stimuli for enhanced neural tissue development is devised. An electrospun piezoelectric poly(vinylidene fluoride‐trifluoroethylene) (P(VDF‐TrFE)) nanofibrous scaffold is systematically optimized to maximize its piezoelectric properties while accommodating the cellular behaviors of neural stem cells. Hydro‐acoustic actuation is elegantly utilized to remotely activate the piezoelectric effect of P(VDF‐TrFE) scaffolds in a physiologically‐safe manner for the generation of cell‐relevant electric potentials. This mechano‐electrical stimulation, which arose from the deflection of the scaffold and its consequent generation of electric charges on the scaffold surface under hydro‐acoustic actuation, induces the multi‐phenotypic differentiation of neural stem cells simultaneously toward neuronal, oligodendrocytic, and astrocytic phenotypes. As compared to the traditional biochemically‐mediated differentiation, the 3D neuron‐glial interface induced by the mechano‐electrical stimulation results in enhanced interactions among cellular components, leading to superior neural connectivity and functionality. These results demonstrate the potential of piezoelectric material‐based technology for developing functional neural tissues in vitro via effective neural stem cell modulation with multi‐faceted regenerative stimuli. Abstract : A piezoelectric material is utilized to electrically stimulate neural stem cells under mechanical perturbation. This mechano‐electrical stimulation induces multiphenotypic differentiation of neural stem cells simultaneously toward neurons and glial cells, resulting in enhanced neural functionality including the induction of neuronal‐glial interaction and enhancement of neural cell functionality.